2018
DOI: 10.3389/fpsyg.2018.00576
|View full text |Cite
|
Sign up to set email alerts
|

Population Size and the Rate of Language Evolution: A Test Across Indo-European, Austronesian, and Bantu Languages

Abstract: What role does speaker population size play in shaping rates of language evolution? There has been little consensus on the expected relationship between rates and patterns of language change and speaker population size, with some predicting faster rates of change in smaller populations, and others expecting greater change in larger populations. The growth of comparative databases has allowed population size effects to be investigated across a wide range of language groups, with mixed results. One recent study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 97 publications
4
39
1
Order By: Relevance
“…6 Population size has become a widely used variable especially in research on language evolution and linguistic diversification (e.g. Lupyan and Dale 2010; see also the excellent review in Greenhill et al 2018 and the references there). Proportion of L2 speakers is not as widely used as a variable owing largely to limitations in data availability, but it is a more direct proxy for effects from intensive language contact on language structure.…”
Section: Sociolinguistic Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Population size has become a widely used variable especially in research on language evolution and linguistic diversification (e.g. Lupyan and Dale 2010; see also the excellent review in Greenhill et al 2018 and the references there). Proportion of L2 speakers is not as widely used as a variable owing largely to limitations in data availability, but it is a more direct proxy for effects from intensive language contact on language structure.…”
Section: Sociolinguistic Variablesmentioning
confidence: 99%
“…Hypotheses about social conditions influencing rates of change have also appeared in evolutionary linguistic research and researchers have begun to test whether rates of change depend on sociolinguistic conditions, such as population size (e.g. Bowern 2010, Greenhill et al 2018, Grollemund et al 2015. In research on cultural evolution, demographic factors, such as population size, play also crucial role since they may influence the rate of cultural innovations, including linguistic ones (Richerson et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the influence of population size on speed of change is not uniform. A recent comparative study confirmed that rates of word loss are significantly greater in smaller languages, but only for the Indo-European family; no effect was found for small languages from other families such as Austronesian or Niger-Congo (Greenhill et al, 2018). This led to the conclusion that either the influence of population size on change rate is not universal or it is weak enough to be mollifiable by other influences (Greenhill et al, 2018).…”
Section: Challenge 6: Speed Of Change In Small Languagesmentioning
confidence: 96%
“…These results provide insight into how the concept of "population" works in online spaces in contrast to physical communities. Previous works show a weak correlation between population of a geographic area and the occurrence of language evolution (Bromham et al, 2015;Greenhill et al, 2018). A limitation of these studies was their inability to account for language output that was not written (i.e, oral communications).…”
Section: Evaluating Semantic Shift To Community Characteristicsmentioning
confidence: 97%